Survey of security for Android smart terminal - Yan-ping XU; Zhao-feng MA; Zhong-hua WANG; Xin-xin NIU; Yi-xian YANG (Tongxin xuebao)
Aiming at the security,the layered security system was constructed.Firstly,the devices safety protection based on remote anti-theft,biometric identity verification and hardware security module was expounded.Secondly,network security referring to the wireless security network,virus propagation killing and anti-phishing was illustrated.Thirdly,the OS safety was introduced from the perspective of system kernel,runtime environment and application framework.Fourthly,application security was showed containing the reverse engineering static analysis,behavior dynamic analysis,safety reinforcement and safety assessment.Fifthly,the privacy data protection was summarized including tracking,encryption and backup.Finally,the future development direction was prospected on the security framework and intelligent behavior analysis.